Persepsi Risiko dan Perilaku Konsumtif: Implikasinya Terhadap Minat Menggunakan Fitur Paylater Pada Traveloka - Defa Febiska; Nuraeni Hadiati Farhani (Sains: Jurnal Manajemen dan Bisnis, 2025)
The development of digital financial technology has introduced innovative payment systems such as Buy Now Pay Later (BNPL), with Traveloka’s TPaylater as one of the emerging services. This study examines how customer risk perception and behavior influence TPaylater usage. SPSS 25 was used for multiple linear regression analysis. A questionnaire was sent to 100 TPaylater users in Greater Jakarta (Jabodetabek). Consumer behavior was measured through impulsive and rational purchasing tendencies, while risk perception was analyzed through five dimensions: financial, performance, privacy, time, and delivery. Consumer behavior, particularly impulsive purchasing, positively impacted user interest in TPaylater, while risk perception did not. These findings suggest that despite awareness of potential risks, consumer tendencies to seek convenience and immediate gratification often override concerns, thereby increasing the likelihood of using such credit-based digital features. Future research is advised to consider additional factors such as financial literacy and social influence, which may further clarify behavioral patterns in digital financial service adoption.